Measurement of maternal cerebral tissue hemoglobin on near‐infrared time‐resolved spectroscopy in the peripartum period. Issue 6 (16th December 2014) - Suzuki, Kazunao; Itoh, Hiroaki; Mukai, Mari; Yamazaki, Kaori; Uchida, Toshiyuki; Maeda, Hideki; Oda, Motoki; Yamaki, Etsuko; Suzuki, Hiroaki; Kanayama, Naohiro
Abstract Aim To measure cerebral tissue hemoglobin in uncomplicated and complicated pregnant women during the peripartum period. Methods Time‐resolved spectroscopy (TRS‐20) can measure absolute concentration of oxygenated, deoxygenated, and total tissue hemoglobin based on the transit time of individual photons. Therefore, we used TRS‐20 to measured tissue hemoglobin in the hemi‐prefrontal lobes of normotensive pregnant women with (n = 51) or without (n = 19) epidural anesthesia, hypertensive pregnant women with pre‐eclampsia (n = 10), a pregnant woman with acute onset of hypertension soon after delivery, and a hypertensive woman after hemorrhagic stroke in delivery. Results Cyclic labor concomitant with intra‐abdominal pressure caused synergistic elevation in cerebral tissue hemoglobin. In contrast, epidural anesthesia reduced the amplitude of the cyclic increase of cerebral tissue hemoglobin in normotensive pregnant women. Hypertension in labor due to pre‐eclampsia increased the amplitude of synergistic elevation of cerebral tissue hemoglobin caused by cyclic labor and intra‐abdominal pressure. A prolonged high basal level of cerebral tissue hemoglobin was observed in a case of acute onset of hypertension soon after delivery. A decrease in cerebral tissue hemoglobin in the hemi‐prefrontal lobe was observed in a woman 2 h after the onset of hemorrhagic stroke in labor. Conclusions TRS‐20 can detect specific changes in maternal cerebral tissue hemoglobin level in response to physiological and pathophysiological changes in delivery. Thus, it represents a promising new conventional tool for maternal cerebral monitoring in the peripartum period.